Social dynamics and affect: investigating within-person associations in daily life using experience sampling and mobile sensing - Krämer, Michael; Roos, Yannick; Schoedel, Ramona; Wrzus, Cornelia; Richter, David (Emotion, 2024)
Social interactions are crucial to affective well-being. Still, people vary interindividually and intraindividually in their social needs. Social need regulation theories state that mismatches between momentary social desire and actual social contact result in lowered affect, yet empirical knowledge about this dynamic regulation is limited. In a gender- and age-heterogenous sample, German-speaking participants (N = 306, 51% women, Mage = 39.41, range 18-80 years) answered up to 20 momentary questionnaires about social interactions and affect while mobile sensing tracked their conversations, calls, and app usage over 2 days. Combining preregistered and exploratory analyses, we investigated how momentary affect relates to social dynamics, focusing on two states of mismatch between social desire and social contact: social deprivation (i.e., being alone but desiring contact) and social oversatiation (i.e., being in contact but desiring to be alone). We used specification curve analyses to scrutinize the operationalization of these constructs. Social oversatiation was associated with decreased positive affect and increased negative affect. Social deprivation, however, was unrelated to affect. Exploratory multilevel models showed that a higher desire to be alone was consistently associated with decreased affective well-being, whereas a higher desire for social contact was related to increased affective well-being. Mobile sensing data revealed differential association patterns between affect and face-to-face versus digital communication. We discuss implications for social need regulation, related studies on voluntary solitude, and advantages of combining experience sampling and mobile sensing assessments. (PsycInfo Database Record (c) 2023 APA, all rights reserved)